Endogenous endophthalmitis secondary to erysipelas. (29th June 2015) - Costa, José F; Marques, João Pedro; Marques, Marco; Quadrado, Maria João
Abstract : A 64-year-old woman with chronic right arm lymphoedema presented with progressive and painful vision loss in the right eye following diagnosis of erysipelas in the ipsilateral arm. Visual acuity was light perception. Biomicroscopy revealed marked conjunctival injection, decreased corneal transparency and an inflammatory mass in the anterior chamber, which precluded fundoscopy. The ocular ultrasonography features were consistent with acute endophthalmitis, and the patient was admitted to the hospital. A systemic evaluation, including complete physical examination, echocardiography and blood tests, ruled out other sources of infection besides the cutaneous site. Blood cultures were positive for group A Streptococcus . A diagnosis of unilateral acute endophthalmitis due to group A Streptococcus bacteraemia secondary to erysipelas was made and successfully treated with optimal medical care, including prompt intravitreal and systemic antibiotic administration. Despite resolution of the infectious process, visual acuity did not improve.